SEGURANÇA ALIMENTAR E NUTRICIONAL NO ENSINO DE CIÊNCIAS: UMA DISCUSSÃO NA PERSPECTIVA DA ALFABETIZAÇÃO CIENTÍFICA - Soneghetti, Elaine Maria (2022)
The main objective of the research is to describe the development of a sequence of didactic activities carried out with a group of students from the 8th year of Elementary School in Serra/ES on the theme "Food and Nutritional Safety", in the discipline of Science, seeking evidence of scientific literacy. The qualitative and collaborative research involved a teacher and her 8th grade students from a Municipal Public School in Serra, ES. The data collection instruments used throughout the study were questionnaires, a logbook and an essay prepared by the students. For data analysis, we opted for content analysis with delimitation of a priori analysis categories based on the scientific literacy axes proposed by Sasseron and Carvalho. We conclude that, from the development of activities on Food and Nutrition Security, we can start a process of Scientific Literacy, enabling the student to carry out a critical reading of the world of himself, others and society and understand phenomena that surrounds him, promoting critical thinking in students. and helping them to make decisions regarding society's problems.